ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL SCREENING OF LEAVES EXTRACT OF MORINDA PUBESCENS LINN. PLANT - Goyal, Rajesh Kumar; Garud, Akanksha; Garud, Navneet (Journal of Drug Delivery and Therapeutics, 2013)
The ethanolic extracts of leaves of Morinda pubescens Linn. were explored for their phytochemical constituents and antimicrobial activity. The preliminary evaluation of ethanolic extract exhibited appreciable antimicrobial activity on the tested pathogenic bacterial isolates at a concentration of 100mg/g and displayed inhibitory potency (20-22mm) in diameter on the tested bacterial isolates. Phenol and alkaloids was found to be present in the plant parts while highest phenolic constituent was recorded in the leaves extract.